Comparison of Distally Based Sural Fasciocutaneous Island Flap with a nd without Inclusion of Sural Nerve - Samuel, Tabish; Hameed, Shahid; Majid, Abdul; Naqvi, Shahid Hussain; Faisal, Shah; Mehmood, Farman (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To compare the inclusion and exclusion of the sural nerve in fascio-cutaneous flap repair for lower extremity reconstruction in terms of flap survival, flap size, recovery of skin sensation and complications.Study Design: Prospective comparative studyPlace and Duration of Study: Department of Plastic Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Jul 2017 to Mar 2020.Methodology: A total of 54 patients (27 in each Group) requiring distal lower limb flap reconstruction and meeting the inclusion and exclusion criteria were included. Patients with a higher probability of flap complications and those with complications during the procedure were excluded. Group-A patients underwent fascio-cutaneous flap repair with sural nerve preservation, while Group-B patients underwent the same technique, but the sural nerve was transected and raised with the flap. All patients were followed for flap survival, flap size and degree of sensory recovery and flap-related complications.Results: Varying degrees of return of sensation were seen in 25(92.6%) patients of Group-A after six months, which was 23(63.1%) in Group-B (p